The mitochondrial genome of the sooty swift (Cypseloides fumigatus) - Renata Neves Biancalana; Cibele Biondo; Fabio Raposo do Amaral (Mitochondrial DNA. Part B. Resources, 2017)
We assembled the mitogenome of Cypseloides fumigatus based on off-target sequences from ultraconserved elements sequencing. We found a total length of 16,850 bp, including 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and one control region, organized in the standard avian gene order. We have built a phylogenetic tree including 26 species of swifts that suggested C. fumigatus as sister species of C. cryptus, and indicated exciting opportunities for biogeographic inferences involving most continents, including Neartic vs Neotropical disjunctions and local radiations across the globe. Finally, we found cases of lack of reciprocal monophyly between named species and high intra-specific divergence, suggesting that population-level studies are warranted.